2004
DOI: 10.1103/physrevb.69.094504
|View full text |Cite
|
Sign up to set email alerts
|

Planar Cu and O hole densities in high-Tccuprates determined with NMR

Abstract: The electric hyperfine interaction observable in atomic spectroscopy for O and Cu ions in various configurations is used to analyze the quadrupole splitting of O and Cu nuclear magnetic resonance ͑NMR͒ in La 2Ϫx Sr x CuO 4 and YBa 2 Cu 3 O 6ϩy and to determine the hole densities at both sites as a function of doping. It is found that in La 2Ϫx Sr x CuO 4 all doped holes ͑x͒ reside in the Cu-O plane, but almost exclusively at O. For YBa 2 Cu 3 O 6ϩy and yϽ0.6 doped holes are found at planar Cu as well as O. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
125
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 40 publications
8
125
0
Order By: Relevance
“…2c). The validity of this assumption is supported by a recent analysis of NMR and atomic spectroscopic results indicating that the doped holes reside almost exclusively on the planar oxygen, and that the EFG is linearly proportional to n p [21]. As seen in Fig.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…2c). The validity of this assumption is supported by a recent analysis of NMR and atomic spectroscopic results indicating that the doped holes reside almost exclusively on the planar oxygen, and that the EFG is linearly proportional to n p [21]. As seen in Fig.…”
supporting
confidence: 64%
“…However, the planar oxygen does not suffer the same fate: it experiences an isotropic transferred hyperfine coupling (129 kOe/µ B ) to the two nearest neighbor Cu spins, so for antiferromagnetically correlated neighbors, the hyperfine field at the O site vanishes [20]. Furthermore, 17 O (I=5/2) has a quadrupolar moment ( 17 Q = -2.56 ×10 −26 cm 2 ), so it is sensitive to the EFG at the nuclear site, which is a measure of the local hole doping [21]. Although previous NMR studies have shown the presence of spatial modulations due to doping inhomogeneities in superconducting La 2−x Sr x CuO 4 [6,8], O NMR in La 1.8−x Eu 0.2 Sr x CuO 4 provides a unique opportunity to investigate the doping inhomogeneity in a system where the spin fluctuations are suppressed.…”
mentioning
confidence: 99%
“…Signal intensity issues have not been properly addressed with most experiments adding to uncertainties. Perhaps the strongest evidence, however, that the observed NMR signals do represent the bulk properties is the fact that the quadrupole splittings measured with NMR account for the average chemical doping [32][33][34].…”
Section: Frequencies Shifts and Splittingsmentioning
confidence: 99%
“…The distribution of local EFGs is directly related to the hole occupation in the O 2p orbitals via the relation ν αα = ν 0 αα + q α n p , where ν 0 αα are material dependent constants, q α = 1.225 MHz for α = (a, c), and 2.452 MHz for α = b, and n p is the hole concentration in the O 2p orbital. 34 Assuming the holes go exclusively into each of these two orbitals, n p = p/2 = 0.105. For a distribution δn p of local hole doping, the quadrupolar contribution to the linewidth would be σ Q = nq α δn p , where n is the particular satellite transition.…”
Section: B Evidence For Electronic Inhomogeneitymentioning
confidence: 99%
“…The dominant contribution arises from this on-site term, and is a direct measure of the doping in the cuprates, which enables us to quantitatively extract the local hole concentration in the oxygen orbitals. 17,34 Susceptibility and resistivity measurements indicate T c = 82 K corresponding to a doping level of p ≈ 0.21. 35 The temperature dependence of the shift, EFG and linewidths were determined by measuring the centers of gravity and second moments n = ±1 satellite transitions.…”
mentioning
confidence: 99%